MANAJEMEN REKRUTMEN GURU DALAM OPTIMALISASI KERJA GURU DI DAYAH JAMIAH AL-AZIZIYAH BATEE ILIEK SAMALANGA - Rizal Fahlevi, Muhammad (ILJ: Islamic Learning Journal, 2024)
This research is based on the background of an institution that always needs new teachers to fulfil the growing quota. The existence of teachers who die, retire and even get sick or absent is the cause of the shortage of teachers that continues to occur every year. In Dayah Jamiah Al-Aziziyah Batee Iliek Samalanga, there is always a shortage of teachers due to the rapid growth of the dayah so it is necessary to recruit new teachers. This research uses a type of qualitative research with a case study approach. The object of this research was carried out at Dayah Jamiah Al-Aziziyah Batee Iliek Samalanga. Data collection techniques using observation, interviews, and documentation. The data sources in this study include the Leader / Kyai, the person in charge of the boarding school, the dayah leader, the Head of Curriculum, the Head of Pengaian, teachers, and students. The analysis techniques used in this research are data collection, data reduction, data presentation, conclusion drawing. Triangulation used to test the validity of the data is triangulation of techniques and sources.The results showed that: a. Understanding the vision and mission of the institution. Understanding the vision and mission of the institution by the recruitment executive committee in order to form a good and qualified teaching staff. b. The formation of the committee. The formation of the committee was carried out in the context of recruiting teachers, Dayah Jamiah Al-Aziziyah Samalanga formed a small team to manage the recruitment of teaching staff. c. Determination of implementation procedures. The implementation procedure is formed by the team or committee itself, the implementation procedure is used as a reference when the recruitment takes place, so that the recruitment will have direction and can focus on the objectives of the activity